PEMANFAATAN SISTEM INFORMASI GEOGRAFIS BERBASIS WEB DALAM KASUS STUNTING MENGGUNAKAN FRAMEWORK LARAVEL - Sri Azizah Nazhifah; Siti Nur Aisha; Muslim Muslim; Kikye Martiwi Sukiakhy; Junidar Junidar (Politeknik Bisnis Indonesia, 2023)
Stunting is a condition that affects the growth of toddlers and occurs when a child is two years old. One of the causes of stunting is a lack of nutritional intake over an extended period. In this case, stunting cases in Bener Meriah Regency rank as the third highest in Aceh province. One of the reasons is the lack of information received by the public regarding stunting. Several negative influences that can lead to stunting include insufficient nutritional intake during pregnancy or for toddlers over an extended period, low levels of education, as well as economic status and childcare services. Therefore, with the existence of this system, individuals affected by stunting can utilize the provided information to understand the distribution of stunting, plan more effective prevention and intervention measures. This WebGIS is built using Laravel, Leaflet, ArcGIS, and tested using a black box to check functionality, ensuring that the system runs smoothly. The testing results of the system show that it is reliable and can be used efficiently. Overall, the implementation of this system can have a positive impact on stunting intervention efforts in Bener Meriah Regency.